1991
DOI: 10.1029/91jb00921
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of Pnl waves from explosions

Abstract: The long‐period character of P nl waves from many tectonic regimes has been modeled in the past using a simple homogeneous layer over a half‐space crust model. Scant attention has been paid to the short‐period wave form character. In this study the P nl waves from Nevada Test Site explosions as recorded on a regional digital seismic array have been modeled in the period range 1–10 s. The fine structure of the P nl waveform has been carefully analyzed. The effects of a realistic velocity gradient at the free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…:ftectivity code developed by Saikia and Burdick (1991). The velocity model consists of two layers over a half space with the Moho at 64 km (Table 2).…”
Section: Data and Resultsmentioning
confidence: 99%
“…:ftectivity code developed by Saikia and Burdick (1991). The velocity model consists of two layers over a half space with the Moho at 64 km (Table 2).…”
Section: Data and Resultsmentioning
confidence: 99%
“…Generally this is done by modifying the overall thickness of the crust and velocities of the crustal layers and the upper-most mantle. The primary upper layer, corresponding to the sedimentary structure, strongly aects the Rayleigh waves and the character of the PL (extended P-wave) and S wavetrains (SONG et al, 1996;SAIKIA, 1994;SAIKIA and BURDICK, 1991). If observations suggest a strong gradient in the velocity structure ± that is, the initial P wave is sharp and impulsive with the character of turning ray rather than the longer period ramp-like head-wave character ± a detailed model with a gradient in the mantle structure must be used (SAIKIA, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…LEFEVRE and HELMBERGER (1989) and HOLT and WALLACE (1989) demonstrated that the P nl analysis procedures can be applied without substantial modi®cation to observations from virtually any tectonic region. In a later study SAIKIA and BURDICK (1991) extended the application to shorter period P nl waves and demonstrated that short-period P nl waves also have many stable features which can be deterministically modeled to characterize the regional crustal waveguide. This characteristic of P nl waves is due to their primarily sampling the lower crust and the Moho interface, and consequently being relatively insensitive to lateral crustal variations, which occur mainly in the upper crust.…”
Section: Methodsmentioning
confidence: 99%
“…We computed synthetic seismograms for a magnitude 7.3 strike-slip earthquake using the synthetic seismogram method described by . We used a fast algorithm for computing Green's functions by frequency-wavenumber integration (Saikia and Burdick, 1991). The ground motions at a site 1.5 km from the fault rupture surface were estimated by averaging the ground motions calculated for a range of different rupture scenarios.…”
Section: Modeling Of Near-fault Long Period Ground Motionsmentioning
confidence: 99%